The potential of abalone stock enhancement in the Eastern Cape Province of South Africa - Godfrey, Brian Peter (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2003)
The largest abalone in South Africa, the perlemoen, Haliotis midae, occurs along approximately two-thirds of the country's coastline, but has only been the target of an extensive commercial fishery in the south-western part of South Africa. Large-scale illegal fishing has however proliferated throughout its entire range over the last 10"“15 years, which has had serious effects on stock abundance and once productive populations are facing economic collapse. Abalone stock enhancement has been put forward as an addition or alternative to traditional fisheries management practices, which can potentially rehabilitate overfished abalone populations and enhance natural production. The aim of this project was to investigate the potential of abalone stock enhancement for managing an area in the Eastern Cape Province, which was being subjected to intense illegal fishing pressure. A research approach was adopted to investigate the scale and effects of this poaching and to investigate the survival of artificially cultured abalone seed in the natural environment. A model of a commercial-scale ranching operation was investigated to assess the economic feasibility of such a scheme. Analysis of poaching cases and research samples from Cape Recife indicated high levels of fishing effort that appeared to be causing the observed declines in emergent abalone abundance and average size. Poaching cases from Cape Recife contributed 32% of the total number of cases of known origin in the Eastern Cape Province from 1998"“2002, with the majority of the cases (82%) originating from within the Port Elizabeth metropole. There was an exponential increase in the number of poaching cases in the Eastern Cape Province (rÂ²=0.967) and Port Elizabeth over this period but actual annual total catch stabilized, particularly at Cape Recife, where estimates of CPUE declined significantly from 2000"“2002 (p<0.001). The annual proportion of emergent abalone under the MLS from Cape Recife was always >85% in confiscations and research collections, and did not change significantly over the period of examination. Comparison of illegal catches with an adjacent site indicated that the emergent abalone population at Cape Recife had a significantly higher proportion of undersized emergent animals (p<0.001) and they were significantly smaller than the abalone from the closest site, Noordhoek, and other areas in Port Elizabeth from 2000"“2002 (p<0.001). The apparent declines in emergent abalone abundance indicated by the poaching data were corroborated by sampling of emergent abalone abundance at Cape Recife. Numbers of abalone declined significantly from 125.6 to 53.8 per 20min count (p<0.001), from April 1998"“October 2001 and density declined from 1.3 to 0.8mâ »Â² over a similar period (p<0.001). Juvenile density did not change over this period, although there were significant differences in density observed between two different habitats (p<0.001). Initial releases of cultured juvenile abalone showed that they could be distinguished from their wild counterparts for at least a year after release, by their different shell colouration. Short-term, small-scale trials (7"“10 days) using animals between 17 and 30mm SL had mean survival rates of 64"“82% (mean 70.4%) and the effect of size on survival was not significant in most cases, although the power to detect differences was low. Attempts to measure the effect of habitat on survival were not conclusive, although refuges under sea urchins appeared to be favoured by both seed and wild abalone, although urchins were not an absolute requirement for survival. Similar medium-term trials (31"“74 days) in sheltered sites yielded mean returns of 53.1% using 25mm SL animals and similar trials in a more exposed area had more variable survival rates of between 18.4 and 73.6%, after 25"“27 days. A comparison between careful hand-seeding and surface-scattering seed release methods in the open-ocean habitat showed no significant differences in survival rate after 41 days. Larger seed survived significantly better than the smaller seed when scattered on the surface (p<0.0001) and the smaller seed survived significantly better when seeded carefully by hand onto the substrate (p<0.028). Further medium-term releases of large numbers of seed abalone, released using the surface-scattering method in open-ocean habitat, gave mean survival rates of 32.8% over periods of 83"“114 days. Assessment of a seeding trial using release modules to seed juvenile animals in the open-ocean was hampered by poor sea conditions and difficult to search substrates, and a mean recovery rate of 3.1% was obtained for the sites that were sampled. Movement of seed was low in the more sheltered sites, and also appeared to be affected by the amount of available habitat. Growth of seed was measured using changes in shell colouration and there were significant differences between areas. An average growth of 1.6mm.monthâ »Â¹ shell length was calculated for all areas. The potential for commercial scale abalone ranching to be used to enhance a territorial user right fishery was investigated using a model of economic feasibility. Internal rates of return of 30.3 and 36.9% were obtained from two harvest regimes using different harvest sizes. There was a high degree of risk associated with these figures owing to a lack of consistent seed survival rate estimates, and the input parameters, which are subject to variation, showed a significant effect on profitability. The operation of this type of ranching scheme is probably not economically feasible as a stand-alone operation but could probably be operated effectively in conjunction with an existing abalone farm. By adding a small wild catch component the profitability of a ranching scheme could be significantly improved. The results of the present study indicate that high levels of poaching at Cape Recife have led to declines in emergent abalone abundance, which will probably lead to stock collapse in the near future. This implies that fisheries managers have failed to fulfil the provisions of fisheries policy in South Africa. The present results from seeding trials show that cultured juveniles can survive and make a contribution to overall stock abundance. Furthermore, while there are obstacles to economic feasibility, commercial ranching has the potential to be a valuable addition to current abalone management strategy.
Keywords: Abalones -- South Africa -- Eastern Cape; Abalone culture; Abalone fisheries -- South Africa -- Eastern Cape